A Danish text-to-speech system using a text normalizer based on morph analysis - Granström, Björn; Molbæk Hansen, Peter; Grønnum Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1988)
A Nordic cooperative project has been started to develop a text-to-speech device for the Nordic languages. The development is based on the system originally created in Stockholm. Language specific features have necessitated modifications of the original structure. For Danish, this primarily involves the inclusion of a morph based "text normalizing component". This paper presents the construction and function of the system and also discusses some preliminary use of the device.